Quản trị nhà trường trong xây dựng môi trường ứng dụng công nghệ thông tin và chuyển đổi số trong dạy học tích cực tại các trường trung học phổ thông Bắc Trung Bộ - Nguyễn Thị Hà, Nguyễn Thị Hà; Trần Xuân Bách, Trần Xuân Bách (Tạp chí Giáo dục, 2026)
The school principal has a positive impact on the quality and effectiveness of teaching through direct influence on the learning environment. The application of information technology and digital transformation in teaching is increasingly important in building a positive learning environment. The purpose of this study is to understand the perceptions of teachers and administrators in several high schools in the North Central region regarding the application of information technology and digital transformation in active teaching, and the implementation of school management content in building such an environment by the principal. The research results show that the application of information technology and digital transformation in active teaching is at an average level. The management content for building an environment applying information technology and digital transformation in active teaching is implemented at a level that does not meet expectations, and the effectiveness achieved is lower than the level of implementation. These results provide an important practical basis for proposing effective measures to improve the management of building an environment for applying information technology and digital transformation in active teaching and learning in high schools.